2019
DOI: 10.1080/10888438.2019.1642894
|View full text |Cite
|
Sign up to set email alerts
|

The Home Literacy Environment in Rural Rwanda and Its Relationship to Early Grade Reading

Abstract: The developing world faces a learning crisis, wherein children fail to master basic skills despite years of primary school attendance. The literature indicates that both in-school and at-home experiences impact children's reading development, yet most developing world studies focus on children's in-school experiences exclusively. This current study addresses this imbalance by exploring the home literacy environment in rural Rwanda and its relationship to children's reading development. The data come from 466 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
0
8
1
Order By: Relevance
“…Bivariate correlations indicated that children who showed high versus low progress in reading did not differ significantly across any component that comprised the HLLE composite (i.e., presence of household reading materials, Bible, household literacy rates, radio or homework help). These findings are not in line with prior work showing positive associations between aspects of children's HLLE and reading progress (Nag et al, 2019;Friedlander, 2020) as they suggest that high and low progressing readers may come from homes with similar language and literacy supports, at least in our study community. Nonetheless, these non-significant associations between HLLE and reading progress status could also be due to limited sample power and thus should be interpreted with caution.…”
Section: Identifying Factors Related To Low Progress In Readingcontrasting
confidence: 99%
See 4 more Smart Citations
“…Bivariate correlations indicated that children who showed high versus low progress in reading did not differ significantly across any component that comprised the HLLE composite (i.e., presence of household reading materials, Bible, household literacy rates, radio or homework help). These findings are not in line with prior work showing positive associations between aspects of children's HLLE and reading progress (Nag et al, 2019;Friedlander, 2020) as they suggest that high and low progressing readers may come from homes with similar language and literacy supports, at least in our study community. Nonetheless, these non-significant associations between HLLE and reading progress status could also be due to limited sample power and thus should be interpreted with caution.…”
Section: Identifying Factors Related To Low Progress In Readingcontrasting
confidence: 99%
“…While most studies have investigated how the quality of HLLE relates to children's learning in developed countries, there is a growing body of research focused on the relevance of HLLE for children's literacy development in developing contexts as well (Nag et al, 2019;Friedlander, 2020;Kim et al, 2020). Recent meta-analyses (Nag et al, 2019;Kim et al, 2020) have found consistent associations between home language and literacy activities and children's literacy acquisition.…”
Section: Theoretical Framework and Literature Review Home Literacy An...mentioning
confidence: 99%
See 3 more Smart Citations